2004
DOI: 10.1086/423732
|View full text |Cite
|
Sign up to set email alerts
|

The Unusual Tidal Dwarf Candidate in the Merger System NGC 3227/3226: Star Formation in a Tidal Shock?

Abstract: We report the discovery of active star formation in the H i cloud associated with the interacting Seyfert system NGC 3227/NGC 3226 that was originally identified as a candidate tidal dwarf galaxy (TDG) by Mundell et al. and that we name J1023+1952. We present broad-band optical B, R, I (from the INT) and ultraviolet images (from XMM-Newton) that show the H i cloud is associated with massive on-going star formation seen as a cluster of blue knots (M B ∼ <−15.5 mag) surrounded by a diffuse ultraviolet halo and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 48 publications
4
62
0
Order By: Relevance
“…Oosterloo et al 2007;Mapelli et al 2008). Clouds and filaments at similar column densities are observed also around other galaxies (Fraternali et al 2002;Mundell et al 2004;Westmeier et al 2005;Sancisi et al 2008). As an aside, a similar increase in the prominence of H I when going to lower column densities is also found for early-type galaxies.…”
Section: Pos(aaska14)129supporting
confidence: 71%
“…Oosterloo et al 2007;Mapelli et al 2008). Clouds and filaments at similar column densities are observed also around other galaxies (Fraternali et al 2002;Mundell et al 2004;Westmeier et al 2005;Sancisi et al 2008). As an aside, a similar increase in the prominence of H I when going to lower column densities is also found for early-type galaxies.…”
Section: Pos(aaska14)129supporting
confidence: 71%
“…The subsequent discovery of a region of very blue star-forming knots with luminosities between 10 6 and 5 ; 10 6 L , embedded in a high H i column density ridge in the southern half of J1023+1952 (Mundell et al 2004), confirmed its classification as a dwarf galaxy; the inferred SFR, UV luminosities, and H equivalent widths of the knots suggested a starburst age less than 10 Myr. Near-infrared imaging provided further evidence for the youth of J1023+1952; no additional embedded star formation or old stellar population were found ( Mundell et al 2004).…”
Section: Introductionmentioning
confidence: 89%
“…Although the edges of the galactic disks of NGC 3227 and J1023+ 1952 spatially overlap in projection (Mundell et al 1995(Mundell et al , 2004, it is possible to disentangle their different kinematic components in the current 12 CO(1Y0) data set. On average, the emission from NGC 3227 is blueshifted by approximately 200 km s À1 with respect to that of J1023+1952, with line widths not in excess of 100 km s À1 , making it possible to separate them by fitting a double Gaussian line profile.…”
Section: Co Datamentioning
confidence: 99%
See 2 more Smart Citations